(3JhTjM GdOjHGL hMdjI GdGHJgGL (B_ (3aj WHbGJ GdeGdcjIs - (3eMeO GdbQGais; (3GHf aQMhf , HQgGf GdOjf,J (B799 (3g` s ((3eMeO Hf eMeO GdecfGS GdTQai s)
(3ChdgG (B:s
(3GdMeO ddg GdMi GdHGbi Ydi GdOhGe hHYO abO SCdfi HYV hNdU NdGfi Cf CVY ef eWGdYGJi PjdkG Ydi cJGH GdYdGeI GHQGgje Hf aQMhf s
(3BNQgG (B:s
(3JQLeI CHj MaU GdRLGLi ef HGH Gdcfi Hbhdg hde JXgQ Hjf Phi GdaVGFd QJHJg hGddg SHMGfg hJYGdi hdi GdCfYGe s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B52 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs